Peritoneal Metastasis After Treated With Abemaciclib Plus Fulvestrant for Metastatic Invasive Lobular Breast Cancer: A Case Report and Review of the Literature - Gao, Hong-Fei; Zhang, Jun-Sheng; Zhang, Qiang-Zu; Zhu, Teng; Yang, Ci-Qiu; Zhang, Liu-Lu; Yang, Mei; Ji, Fei; Li, Jie-Qing; Cheng, Min-Yi; Niu, Gang; Wang, Kun (Frontiers in Endocrinology, 2021)
Peritoneal metastases from invasive lobular carcinoma (ILC) of breast are uncommon and usually related to poor prognosis due to difficulty of detection in clinical practice and drug resistance. Therefore, recognizing the entities of peritoneal metastases of ILC and the potential mechanism of drug resistance is of great significance for early detection and providing accurate management. We herein report a case of a 60-year-old female who presented with nausea and vomiting as the first manifestation after treated with abemaciclib (a CDK4/6 inhibitor) plus fulvestrant for 23 months due to bone metastasis of ILC. Exploratory laparotomy found multiple nodules in the peritoneum and omentum, and immunohistochemistry confirmed that the peritoneal metastatic lesions were consistent with ILC. Palliative therapy was initiated, but the patient died two months later due to disease progression with malignant ascites. Whole exome sequencing (WES) was used to detect the tumor samples and showed the peritoneal metastatic lesions had acquired ESR1 and PI3KCA mutations, potentially explaining the mechanism of endocrine therapy resistance. We argue that early diagnosis of peritoneal metastasis from breast cancer is crucial for prompt and adequate treatment and WES might be an effective supplementary technique for detection of potential gene mutations and providing accurate treatment for metastatic breast cancer patients.